THE RELATIONSHIP OF FAMILY EMOTIONAL SUPPORT TO THE SELF-ESTEEM OF LEPROSY PATIENTS - Edy Suyanto (Jurnal Keperawatan Terapan, 2024)
Infection of leprosy patients poses many challenges, these are transmission process is unclear and the incubation period is long, leprosy patients are prone to mental health disorders, disability due to leprosy causes the emergence of stigma that can reduce the productivity and quality of life of leprosy patients. This can be an obstacle for a leper to carry out his daily activities. Therefore, family support is needed to increase the self-esteem of leprosy patients, so that a leprosy patient has the ability to live his life. The purpose of this study is to determine the relationship between family emotional support and patient self-esteem in skin and venereal clinics. This study uses observational analytical research with a cross sectional study design. Its used purposive sampling technique, namely l43 patients. Data collection was carried out by distributing questionnaires for 3 months. The results shows that the result of Spearman Ranks Test is p<0.001 which means there is a significant relationship between family emotional support and the self-esteem of leprosy patients in the Skin and Venereal clinic. Family emotional support is one of the efforts to improve the coping strategy of leprosy patients because with family support, leprosy patients will feel valued, loved and part of the family